PENGEMBANGAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR INFORMATIKA SISWA SMK - Oktapia, Vina; Lisa, Yasinta; Tuah, Yayan Adrianova Eka (STKIP Persada Khatulistiwa Sintang, 2024)
This research is research into the development of learning media by utilizing articulate storylines to improve student learning outcomes in computer systems material. So far, the learning carried out still does not use learning media because teachers more often use conventional learning media, causing students to be less able to explore in learning. The research method refers to development research using the ADDIE model. The results of the product feasibility test by media experts and material experts obtained an average score of 76.04% on the